Alternative fabrication routes toward oxide-dispersion-strengthened steels and model alloys - Grant, P; Connolly, S; Hong, Z; Bergner, F; Hilger, I; Virta, J; Lagerbom, J; Gerbeth, G; Weissgärber, T (Springer, 2016)
The standard powder metallurgy (PM) route for the fabrication of ODS steels involves the gas atomization to produce a pre-alloyed powder, mechanical alloying (MA) with fine oxide powders, consolidation, and finally thermal/thermo-mechanical treatment. It is well-established that ODS steels with superior property combinations, for example creep and tensile strength, can be produced by this PM/MA route. However, the fabrication process is complex and expensive, and the fitness for scaling up to the industrial scale is limited. At the laboratory scale, production of small amounts of well-controlled model systems continues to be desirable for specific purposes, such as modelling-oriented experiments. Thus, from the laboratory to industrial application, there is growing interest in complementary and/or alternative fabrication routes for ODS steels and related model systems, which offer a different balance of cost, convenience, properties and scalability. This paper reviews the state of the art in ODS alloy fabrication and identifies promising new routes towards ODS steels. The PM/AM route for the fabrication of ODS steels is also described as it is the current default process. Hybrid routes that comprise aspects of both the PM route and more radical liquid metal (LM) routes are suggested to be promising approaches for larger volumes and higher throughput of fabricated material. Although similar uniformity and refinement of the critical nanometer-sized oxide particles has not been yet demonstrated, ongoing innovations in the LM route are described, along with recent encouraging preliminary results for both extrinsic nano-oxide additions and intrinsic nano-oxide formation in variants of the LM route. Finally, physico-chemical methods such as ion beam synthesis are shown to offer interesting perspectives for the fabrication of model systems. As well as literature sources, examples of progress in the authors’ groups are also highlighted.